PERLINDUNGAN HUKUM BAGI PEMBELI PERUMAHAN ATAS SENGKETA KEPEMILIKAN TANAH SETELAH ADANYA PENGIKATAN JUAL BELI RUMAH DARI PIHAK DEVELOPER DITINJAU DARI KITAB UNDANG-UNDANG HUKUM PERDATA (STUDI KASUS PUTUSAN NOMOR:566/Pdt.G/2010/PN.Jkt-Sel) - IRSAN AKHBAR (PREMISE LAW JURNAL, 2017)
ABSTRACT The objective of the research was to analyze the aspect of legal protection granted by the Civil Code for housing customers against a dispute over land title between a developer and a third party after PJB (Sales Contract) has been made between the customer and the developer. It is concluded, based on the research results and discussions, that the force that binds a PJB made between the developer and the customers when the dispute over land title emerges mostly depends on the form of the deed; whether it is an authentic or underhanded one. It is recommended that the parties involved in the making of the PJB before the Notary really understand the agreed clause so that all contents of the PJB Deed can be known and comprehended by both parties. Keywords: Legal Protection, Sales Contract, Housing Customer